Development of Adventure-Based Learning Game on the Topic of Temperature and Heat - Apit Fathurohman; Alfarizi Ade Karlin Kusuma (Universitas Negeri Makassar, 2023)
It has successfully developed an adventure-based learning game on temperature and heat material for junior high schools that is valid and interesting. This research uses the Rowntree development model, which consists of a planning stage, development stage, and evaluation stage. The evaluation stage uses Tessmer's formative evaluation, namely self-evaluation, expert review, one-to-one evaluation, and small group evaluation. Data collection techniques used are walkthroughs and student responses questionnaire sheets. The results of the expert review obtained an average value of 95% with very valid criteria. The results of the one-to-one evaluation stage, students' responses to the use of game learning obtained an average value of 90% with very interesting criteria. Meanwhile, in the small group evaluation stage, students' responses to the use of game learning obtained an average value of 100% with very interesting criteria. Based on the results of these studies, it can be concluded that the adventure-based learning game on temperature and heat material for SMP that was developed is included in very valid and very interesting criteria.